A Promoter Region Mutation Affecting Replication of the Tetrahymena Ribosomal DNA Minichromosome - Gallagher, Renata C. (American Society for Microbiology, 1998)
In the ciliated protozoan Tetrahymena thermophila the ribosomal DNA (rDNA) minichromosome replicates partially under cell cycle control and is also subject to a copy number control mechanism. The relationship between rDNA replication and rRNA gene transcription was investigated by the analysis of replication, transcription, and DNA-protein interactions in a mutant rDNA, the rmm3 rDNA. The rmm3 (for rDNA maturation or maintenance mutant 3) rDNA contains a single-base deletion in the rRNA promoter region, in a phylogenetically conserved sequence element that is repeated in the replication origin region of the rDNA minichromosome. The multicopy rmm3 rDNA minichromosome has a maintenance defect in the presence of a competing rDNA allele in heterozygous cells. No difference in the level of rRNA transcription was found between wild-type and rmm3 strains. However, rmm3 rDNA replicating intermediates exhibited an enhanced pause in the region of the replication origin, roughly 750 bp upstream from the rmm3 mutation. In footprinting of isolated nuclei, the rmm3 rDNA lacked the wild-type dimethyl sulfate (DMS) footprint in the promoter region adjacent to the base change. In addition, a DMS footprint in the origin region was lost in the rmm3 rDNA minichromosome. This is the first reported correlation in this system between an rDNA minichromosome maintenance defect and an altered footprint in the origin region. Our results suggest that a promoter region mutation can affect replication without detectably affecting transcription. We propose a model in which interactions between promoter and origin region complexes facilitate replication and maintenance of the Tetrahymena rDNA minichromosome.